The Effect Of Nutritional Education On Compliance Consuming Iron Tablets In Pregnant Women - Wulandari, Novianti Dewi; Iwan, Sugeng (NUTRITURE JOURNAL; Vol 3 No 3 (2024): Nutriture Journal, 2024)
Anemia in pregnancy is a national problem because it reflects the value of the socio-economic welfare of the community, and has a very large influence on the quality of human resources. Anemia of pregnancy is called "potential danger to mother and child" (potential to harm mother and child), that's why anemia requires serious attention from all parties involved in health services. pregnant women experienced an increase from the previous year which was 48.9% from the previous 37.1% in 2013 and it can be concluded that the proportion of anemia in pregnant women increased by 11.8% over a period of 5 years from 2013 to 2018. A total of 84 ,6% of anemia in pregnant women occurs in the age group 15-24 years. The coverage of giving iron tablets to pregnant women in Indonesia in 2018 was 81.16%. This figure has not reached the 2018 Strategic Plan target of 95%. Objective : To analyze the effect of nutrition education on adherence to consuming iron tablets in pregnant women. Methods : Literature Review Study of journal articles that meet the inclusion and exclusion requirements in the search database using Google Scholar, DOAJ and Garuda using keywords: counseling, knowledge, compliance, pregnant women and anemia. Result : In the 10 articles studied, the majority of the p value of knowledge and adherence to iron tablet consumption <0.05 which means that there is an influence between counseling and adherence to iron tablet consumption of pregnant women. Conclution : There is a significant relationship between counseling adherence to iron tablet consumption of pregnant women.